Fabrication and characterization of carbon nanocomposite based field emission X-ray devices - Yu, Siu Fung. (2012)
Carbon nanotubes (CNTs) have been produced on silicon wafer by filtered cathodic vacuum arc technique using cobalt-containing graphite targets followed by thermal chemical vapor deposition. The Co-containing amorphous carbon (a-C:Co) composite films have various contents of Co as a catalyst for CNTs growth. It is found that dense and random CNTs were grown on the a-C:Co composite film deposited using a 2 at.% Cocontaining graphite target and nanoforest CNTs on the composite films using 5, 10 and 15 at.% Co-containing targets. The nanoforest CNTs using a 15 at.% Co-containing target have very good field emission properties with a low threshold field of 1.6 V/Am and a high and stable current density of 2.1 mA/cm2 at 3 V/Am, which may result from the smaller diameter of CNTs. It is found that the field emission properties of the CNTs are significantly affected by the diameter of CNTs rather than its orientation. An x-ray source was built in a diode configuration using the CNTs as its cold electron source showing good potential in x-ray radiography.